2019
DOI: 10.1515/psr-2018-0169
|View full text |Cite
|
Sign up to set email alerts
|

“Drug-likeness” properties of natural compounds

Abstract: Abstract Our previous work was focused on the fundamental physical and chemical concepts behind “drug-likeness” and “natural product (NP)-likeness”. Herein, we discuss further details on the concepts of “drug-likeness”, “lead-likeness” and “NP-likeness”. The discussion will first focus on NPs as drugs, then a discussion of previous studies in which the complexities of the scaffolds and chemical space of naturally occurring compounds have been compared with synthetic, semisynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…All other compounds showed between two and four violations; however, studies have shown that if a natural product is used as a guiding structure for the production of a synthetic drug such that molecular descriptors (like MW, clogP etc.) can be controlled, that is, the best of both natural and synthetic compounds can be taken into account to obtain a drug that is both harmless to the human body and effective on the virus [ 76 ]. Based on this range, all the 16 compounds qualify as drug-like compounds with nRB values lesser than and equal to 10 [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…All other compounds showed between two and four violations; however, studies have shown that if a natural product is used as a guiding structure for the production of a synthetic drug such that molecular descriptors (like MW, clogP etc.) can be controlled, that is, the best of both natural and synthetic compounds can be taken into account to obtain a drug that is both harmless to the human body and effective on the virus [ 76 ]. Based on this range, all the 16 compounds qualify as drug-like compounds with nRB values lesser than and equal to 10 [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The drug-likeness model score of the UDP-Glucose ligand was found to be 0.93, as might be observed in Figure 4 A. Drug likeliness is a complex qualitative factor that determined bioavailability of a ligand for its substrate [ 65 ]. A positive scoring indicates our ligand fit for the substrate interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Drug-likeness is a quantitative concept used to describe molecules that possess functional groups, chemical and physicochemical properties consistent with most of the approved drugs [ 71 , 72 ]. It provides an insight into the early identification of chemical compounds that are “most likely to succeed” in the drug development venture.…”
Section: Cheminformatics Techniques In Antimicrobial Drug Discovery and Developmentmentioning
confidence: 99%
“…Natural products, chemical entities produced by living organisms, tend to break these established drug-likeness rules obtained from synthetic chemical libraries. The concept of natural product-likeness has been reported to have the potential to open new opportunities for drug discovery from natural compounds while neglected by the drug-likeness rule [ 72 ].…”
Section: Cheminformatics Techniques In Antimicrobial Drug Discovery and Developmentmentioning
confidence: 99%